2021
DOI: 10.1186/s13018-021-02279-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative bone single-photon emission computed tomography imaging for uninfected nonunion: comparison of hypertrophic nonunion and non-hypertrophic nonunion

Abstract: Background Recently, a standardized uptake value (SUV) has been used to evaluate bone single-photon emission computed tomography (SPECT). The aim of this study was to investigate quantitative SPECT imaging of uninfected nonunion to compare hypertrophic nonunion and non-hypertrophic nonunion using volume-based parameters. Methods We evaluated 23 patients with uninfected nonunion who underwent SPECT acquisition 3 h after an injection of 99mTc-hydroxy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The results suggested that the NHNCs have characteristics similar to those of cells from both hypertrophic nonunion and pseudoarthrosis tissues, which have been shown to resemble BMSCs [ 6 , 7 ]. However, the results of Alizarin Red S staining compared with the RIA-derived cells revealed that the NHNCs were less calcified than the BMSCs, which might explain why NHNCs do not show callus formation on X-ray findings [ 5 ]. Based on the results of the real-time RT-PCR, we consider that this might also occur because the expression of OSX , BSP , and OCN is not upregulated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggested that the NHNCs have characteristics similar to those of cells from both hypertrophic nonunion and pseudoarthrosis tissues, which have been shown to resemble BMSCs [ 6 , 7 ]. However, the results of Alizarin Red S staining compared with the RIA-derived cells revealed that the NHNCs were less calcified than the BMSCs, which might explain why NHNCs do not show callus formation on X-ray findings [ 5 ]. Based on the results of the real-time RT-PCR, we consider that this might also occur because the expression of OSX , BSP , and OCN is not upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Non-hypertrophic nonunion was defined as nonunion without radiological callus formation including oligotrophic, comminuted (torsion-wedge, dystrophic, and necrotic), defect, and atrophic types in the Weber and Cech classification and was confirmed by three senior orthopedic trauma surgeons [ 3 , 5 ]. Five patients with non-hypertrophic nonunion surgically treated in our institution were enrolled ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of marked callus formation around the nonunion site typically indicates biological activity; however, in cases without callus formation, it is very difficult to determine the existence of biological activity using only X-ray findings. We previously quantified nonunion fracture repair in terms of the standardized uptake value (SUV) of single-photon emission computed tomography (SPECT) in hypertrophic and non-hypertrophic nonunions [6]. We found high SUVs in cases of non-hypertrophic nonunion, which usually exhibit poor biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests the existence of biological activity. Therefore, we believe that bone SPECT quantification will be useful in autologous bone grafting during nonunion surgery [6,7].…”
Section: Introductionmentioning
confidence: 99%